Observance of the Five Precepts and Their Impact on Modern Society: An Analytical Study - Pun, Debu Kumari (NPRC Journal of Multidisciplinary Research, 2025)
Background: In an era of increasing social and ethical challenges in modern society, there is a growing need to re-examine timeless moral frameworks. The Five Precepts (Pañcasīla), a foundational ethical code in Buddhism, provide a comprehensive guide for individual conduct and social harmony. While rooted in ancient teachings, their applicability to contemporary issues like violence, economic injustice, familial disintegration, and substance abuse warrants detailed academic investigation. Objective: This study aims to analytically investigate the philosophical foundations and practical applications of the Five Precepts. Its primary objective is to assess their impact on fostering personal well-being and social stability, and to analyze the consequences of their violation in the context of modern societal problems. Methods: This research employs a qualitative, analytical design based on a systematic review of primary and secondary sources. Primary data were drawn from the Tipiṭaka (the Pali Canon), including the Sutta Piṭaka (e.g., Aṅguttara Nikāya, Dīgha Nikāya) and the Jātaka tales. Secondary data were gathered from scholarly books, articles, and treatises on Buddhist ethics. A thematic analysis was conducted to synthesize the teachings and their contemporary relevance. Analysis: The analysis reveals that each of the Five Precepts directly addresses a key area of modern social dysfunction: non-violence counteracts a culture of harm; abstaining from stealing promotes economic justice; sexual misconduct’s prohibition underpins family stability; truthfulness is the bedrock of social trust; and avoiding intoxicants ensures personal and public safety. The study establishes a clear correlation between the observance of these precepts and outcomes of personal peace, mental clarity, and communal harmony, while their violation is linked to societal decay. Conclusion: The Five Precepts offer a robust, timeless ethical model that is profoundly relevant for addressing contemporary global challenges. Their practice is concluded to be a critical pathway for achieving sustainable peace, moral integrity, and holistic well-being at both the individual and collective levels, providing actionable guidance for personal development and social policy. Novelty: This study provides a novel, multidisciplinary synthesis of classical Buddhist ethics with modern sociological and psychological challenges. It moves beyond a purely theological discussion, positioning the Five Precepts as a viable, evidence-based framework for interdisciplinary research in ethics, peace studies, and social development.